Fuel Subsidy Imbroglio and Economic Prosperity of Nigeria: A Dynamic Auto Regressive Distributed Lag (DARDL) Approach - Dike, Jude Okechukwu; Obuareghe, Goddey; Eriemo, Nathaniel Oke (PT. Riset Press International, 2025)
This study evaluates the impact of fuel subsidy imbroglio on Nigeria's economic prosperity, covering the period from 1986 to 2022. In investigating the effect of oil subsidy on the economic prosperity of Nigeria, it uses RGDP as the regressed while the regressors are Subsidy Payment (SY). Additionally, Oil rent (RO), Exchange Rate (ER) and institutional variables such as Political stability (PS) and Control of Corruption (CO) served as control variables. To mediate the effect of subsidy, the institution of regulation was applied to moderate the nexus between subsidy payment and economic prosperity in Nigeria (SY*RQ). Data were obtained from secondary sources such as The Central Bank of Nigeria (CBN) Statistical Bulletin, the World Bank Development Index (WDI) and United States Energy Information Administration (USEIA). The dynamic autoregressive distributed lag (DARDL) model estimator tool was deployed for data analysis. The short-run result shows the magnitude of change in economic prosperity orchestrated by political stability. Also, corruption control was effective in the short run and encouraged economic prosperity. At the same time, oil subsidies harmed the country's economic prosperity; as the short-run coefficient implied, the effort to control subsidies directly using the institution of regulation (RQ) failed. Further, the normalized ARDL long-run test shows that the payment of oil subsidies has a minimal impact on economic prosperity in Nigeria. Similarly, when oil subsidy payment is subjected to regulations, its impact is still minimal. Notwithstanding, PS and LEX significantly promote economic prosperity in Nigeria. Based on the findings, the study recommends and supports the removal of fuel subsidies and that the proceeds should be re-invested in providing critical amenities and infrastructure to grow the Nigerian economy.